2016
DOI: 10.1128/iai.01082-15
|View full text |Cite
|
Sign up to set email alerts
|

The First Histidine Triad Motif of PhtD Is Critical for Zinc Homeostasis in Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is the world's foremost human pathogen. Acquisition of the first row transition metal ion zinc is essential for pneumococcal colonization and disease. Zinc is acquired via the ATP-binding cassette transporter AdcCB and two zinc-binding proteins, AdcA and AdcAII. We have previously shown that AdcAII is reliant upon the polyhistidine triad (Pht) proteins to aid in zinc recruitment. Pht proteins generally contain five histidine (His) triad motifs that are believed to facilitate zinc bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Examination of the PhtD solution structure and the homology models of HT2, HT4 and HT5 regions reveals that, similar to PhtD 269-339 , all these fragments possess charged surfaces and would suggest protein surface localization. This structural composition would be consistent with the contribution of these motifs to Zn 2+ acquisition at the pathogen-host interface [11,15]. Notably, the histidine triad residues in HT3 are on a b-hairpin, and as such it would be expected that the conformation of this region would be largely stable in the absence of Zn 2+ .…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Examination of the PhtD solution structure and the homology models of HT2, HT4 and HT5 regions reveals that, similar to PhtD 269-339 , all these fragments possess charged surfaces and would suggest protein surface localization. This structural composition would be consistent with the contribution of these motifs to Zn 2+ acquisition at the pathogen-host interface [11,15]. Notably, the histidine triad residues in HT3 are on a b-hairpin, and as such it would be expected that the conformation of this region would be largely stable in the absence of Zn 2+ .…”
Section: Discussionsupporting
confidence: 61%
“…Recent work by Eijkelkamp et al . revealed a hierarchy for the five HT motifs of PhtD with respect to their importance for in vitro Zn 2+ acquisition. That work showed that HT1 of PhtD, which is closest to the pneumococcal cell membrane, was the most important, whereas HT5 had the smallest contribution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…methyltransferases, zinc finger transcriptional factors and deoxycytidylate deaminases). Proteins specific to ERM fungi included enzymes involved in resistance to environmental stress, such as isochorismate synthase (Sadeghi et al, 2013) and histidine triad domain-containing proteins (Eijkelkamp et al, 2016).…”
Section: Researchmentioning
confidence: 99%
“…The difficulty of implementing this requirement was illustrated by a recent Phase II clinical trial of a combination of 10 polysaccharides with the histidine triad protein PhtD and a pneumolysin toxoid [12]. PhtD is believed to participate in zinc homeostasis in the nasopharynx, and the toxin pneumolysin causes damage to respiratory epithelial cells during pneumonia; both vaccine antigens decreased nasopharyngeal carriage in preclinical models [13,14]. However, the only functional assay developed to test sera after this combined vaccine was not directed to mucosal activity, but rather focused on assessment of complement-mediated killing by leukocytes [15].…”
Section: Multi-modal Protection: Protein Functions Enter the Vaccine mentioning
confidence: 99%